2015
DOI: 10.1371/journal.pntd.0003616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of the Gender Differentials Risk Factors of Child Deaths in Bangladesh: Evidence from the Bangladesh Demographic and Health Survey, 2011

Abstract: BackgroundThe number of child deaths is a potential indicator to assess the health condition of a country, and represents a major health challenge in Bangladesh. Although the country has performed exceptionally well in decreasing the mortality rate among children under five over the last few decades, mortality still remains relatively high. The main objective of this study is to identify the prevalence and determinants of the risk factors of child mortality in Bangladesh.MethodsThe data were based on a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 13 publications
13
27
1
Order By: Relevance
“…Previous studies found a similar association between birth interval and child mortality [12,27,28,[49][50][51].…”
Section: Descriptive Statisticssupporting
confidence: 69%
“…Previous studies found a similar association between birth interval and child mortality [12,27,28,[49][50][51].…”
Section: Descriptive Statisticssupporting
confidence: 69%
“…According to BDHS report (2014), coverage of child vaccinations of major preventable diseases (tuberculosis, diphtheria, pertussis, tetanus, polio, measles) and vitamin A supplementation is lower in Sylhet which may directly affect the immunity system of the children resulting high child morbidity and mortality. Under both models, maternal education (higher education) has strong inverse relationship with under-five mortality and this results have been found similar to the previous studies (Hossain et al 2015, Chowdhury et al 2010, Rahman 2008 conducted in Bangladesh. This may happen due to the facts that female literacy enhances maternal awareness about child immunization, child nutrition and facilitates their access to modern child health care services Alva 1998, Vikram et al 2012).…”
Section: Semiparametric Survival Regression Analysissupporting
confidence: 88%
“…Based on some previous studies (Chowdhury 2013, Hossain et al 2015, Islam et al 2013, Karmaker et al 2014, Muriithi and Muriithi 2015, Nasejje et al 2015, Nisar and Dibley 2014, Kumar and File 2010, Rahman 2008 ), a set of explanatory variables are selected in this study. Mother's age at birth (< 20 years, 20 -30 years, > 30 years), region (Barisal, Chittagong, Dhaka, Khulna, Rajshahi, Rangpur and Sylhet ), mother's education (no education, primary, secondary, higher), wealth index (poor, middle, rich) , birth order number (first birth, others), gender of the child (male, female), place of residence (urban, rural), place of delivery (hospital/clinic, others), mother's membership of Non-Government Organizations (NGO) (member, non-member), child's size at birth (small, average to large), access to media (exposure, non-exposure) are the variables considered to analyze under-five child mortality data in Bangladesh.…”
Section: Data and Variablesmentioning
confidence: 99%
“…The odds of child mortality among the children with PBI <24 months were nearly twice those of children with PBI ≥24 months. Many previous studies found a similar association between short preceding birth interval and increased risk of child mortality [7,33,[51][52][53][54].…”
Section: Specific Combinations Of Risk Factors Of High-risk Fertilitysupporting
confidence: 53%